Recueil, traçabilité et restitution des données territoriales du programme ESPON - Ronan Ysebaert; Isabelle Salmon; Benoit Le Rubrus; Camille Bernard (M@ppemonde)
The ESPON M4D Project entails gathering, verifying, integrating and presenting the territorial data produced by ESPON Applied Research Projects. The main challenges that the project faced were ﬁrstly managing, standardising and coordinating a wealth of diverse data, ensuring data quality and traceability. The second hurdle was the creation of tracking and display tools for territorial data. Implementing specialised methods and tools has provided solutions and opportunities for further analysis in the same ﬁeld of applied research (data center creation, coordination of several data providers).